Lexical-semantic peculiarities of modern kazakh names (Eurasian Journal of Philology Science and Education, 2018)
This article presents the lexical and semantic classification of modern anthroponymy of the Kazakhlanguage on the material of personal names and surnames. Taking into account the tradition of lexicalsemantic classification of anthroponyms (V. N. Nikonov, T. Zhanuzakov),analyzing the data obtainedfrom the Civil Status Department make it possible to divide modern personal names intodifferent groups:a) descriptives; b) desideratives; c) memoratives; g) cultural-historical (social) names. In turn, these categories of names are subdivided into narrower thematic subgroups.As a result of data analysis we offerto include a new subgroup titled modern (transformed) names to the group of cultural-historical (social)names. The analysis of the factual documents of the Department of civil registration of Almaty city for theperiod from 2000 to 2010 provides an opportunity to identify changes in the lexical and semantic systemof modern Kazakh anthroponymy. Scientific observations indicate that in the system of personal namesthere is a revival of indigenous, national names, activationof harmonious traditional personal names andemergence of new borrowed ones.